A Case with Pancytopenia: The Role of Cytomorphology - Lugyanti Sukrisman; Nadia A Mulansari; Aru W Sudoyo (Acta Medica Indonesiana)
A 63-year year old lady presented with prolonged fever, frequent abdominal pain and a history of melena. Physical findings revealed an anemic appearance and splenomegaly. She was treated by the gastroenterologist and subsequently referred to the hematologist as the peripheral blood count revealed pancytopenia with a hemoglobin level of 6.5 g/dl, WBC 4000/ uL and a platelet count of 50.000 /uL. No blast cells were found. Patient subsequently underwent a marrow aspiration. Cytomorphology assessment of the marrow specimen revealed the presence of abnormal megakaryocytes and leukocytes (see figures) which was in accordance with dyshematopeosis, and the diagnosis of MDS (myelodysplatic syndrome) was established. The patient was then started on thalidomide 100 mg daily. There was no significant complications nor side-effects and after almost 2 years her hemoglobin level is now normal (between 12 and 14 g/dl), a dramatic reversal of her condition.